2019
DOI: 10.3390/cancers11070963
|View full text |Cite
|
Sign up to set email alerts
|

Machilin A Inhibits Tumor Growth and Macrophage M2 Polarization Through the Reduction of Lactic Acid

Abstract: Lactate dehydrogenase A (LDHA) is an important enzyme responsible for cancer growth and energy metabolism in various cancers via the aerobic glycolytic pathway. Here, we report that machilin A (MA), which acts as a competitive inhibitor by blocking the nicotinamide adenine dinucleotide (NAD) binding site of LDHA, suppresses growth of cancer cells and lactate production in various cancer cell types, including colon, breast, lung, and liver cancers. Furthermore, MA markedly decreased LDHA activity, lactate produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…The compound 10 is a moderate perpetrator of drug-drug interactions based on their inhibition of the most abundant CYP450 enzymes, such as 1A2 and 2C19. The compound 2 exhibits a simple structure with one 1,3-benzodioxole group compared to the previously reported Machilin A 16 , containing two 1,3-benzodioxole groups. Furthermore, it has a lower LDHA IC 50 value compared to Machilin A (84 µM).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…The compound 10 is a moderate perpetrator of drug-drug interactions based on their inhibition of the most abundant CYP450 enzymes, such as 1A2 and 2C19. The compound 2 exhibits a simple structure with one 1,3-benzodioxole group compared to the previously reported Machilin A 16 , containing two 1,3-benzodioxole groups. Furthermore, it has a lower LDHA IC 50 value compared to Machilin A (84 µM).…”
Section: Resultsmentioning
confidence: 66%
“…Intracellular LDHA activity assay. To observe the LDH activities from the lysates of cells, we performed in accordance with previous studies 16,18 . Briefly, Total protein from lysate (1 μg) was mixed with containing 20 mM HEPES-K + , 20 μM NADH, 2 mM pyruvate.…”
Section: Synthesis Of Compound 10mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the crystal structures, the allosteric transition by the activator within two subunits is not required for the LDHB activity. Recently, machilin A (MA) has been reported to bind to LDHA in an interfacial allosteric site close to the FBP binding site 27 . However, its binding conformation of MA remains controversial because steric clashes of the protein-ligand interactions have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…LDHA (lactate dehydrogenase A) is a vital enzyme responsible for cancer growth and energy metabolism via the aerobic glycolytic pathway. Inhibition of LDHA could inhibit tumor-initiating cell survival and proliferation, which indicated that LDHA may be a potential therapeutics target [27]. GK1 (phosphoglycerate kinase 1) is an important enzyme in the metabolic glycolysis pathway.…”
Section: Discussionmentioning
confidence: 99%